Circular polarization folded reflectarray antenna for 5G applications - Mohd Fairus Mohd Yusoff; Lim Jit Min; Mohamad Rijal Hamid; Zaharah Johari; Muhammad Naeem Iqbal (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Fifth-generation (5G) is a wireless connection built specifically to keep up with the rapid increase of devices that need a mobile internet connection. A system working on 5G band can provide higher bandwidth and faster data rate as compared to fourth-generation (4G) band. Thus, an antenna with higher gain and lower profile is required to support this system. On the other hand, the performance of circular polarization antenna is better than linear polarization antenna due to its ability to accept wave from different direction. In this project, a low profile circular polarization folded reflectarray antenna with operating frequency of 28 GHz is presented. This project is divided into two parts. In the first part, a linear polarization folded reflectarray antenna is designed. In this second part, a meander lines polarizer is used to convert the linear polarization antenna to circular polarization antenna. The antenna is fed by a linear polarized waveguide. Each radiating element of the antenna is in rectangular shape. The size of the radiating elements are selected according to obtain required phase delay to form a planar phase front in the far-field distance. Both of the antennas are simulated by using Computer Simulation Technology (CST) software. Finally, the results shows excellent performances with 16.81dB directivity and 1.49dB axial ratio at 28GHz. Thus, the antenna is very suitable for 5G applications.